Tradisi Kenabian: Relasi Perjanjian Lama dan Perjanjian Baru dalam terang Dokumen Komisi Kitab Suci - Sanjaya, V. Indra (Jurnal Orientasi Baru, 2012)
Christianity has taken the Hebrew Bible as part of its scriptures. This, unavoidably, creates a long time discussion with regard to the relationship between the Old and the New Testament. One of the most popular understanding is to consider the New Testament as the fulfillment of what has been proclaimed in the Old Testament. The teaching of the Church, delivered through various documents, comfirms this popular notion, though not always explicit. However, a document from the Pontifical Biblical Commission published in 2002, shows a particular nuance. This article sought to read it carefully and to draw some practical implications.